The association between genome‐wide polymorphisms and chronic postoperative pain: a prospective observational study. (5th January 2020) - van Reij, R. R. I.; Hoofwijk, D. M. N.; Rutten, B. P. F.; Weinhold, L.; Leber, M.; Joosten, E. A. J.; Ramirez, A.; van den Hoogen, N. J.; ,
Abstract : Summary: Chronic postoperative pain is common and can have a negative impact on quality of life. Recent studies show that genetic risk factors are likely to play a role, although only gene‐targeted analysis has been used to date. This is the first genome‐wide association study to identify single‐nucleotide polymorphisms associated with the development of chronic postoperative pain based on two independent cohorts. In a discovery cohort, 330 women scheduled for hysterectomy were genotyped. A case–control association analysis compared patients without chronic postoperative pain and the 34 who had severe chronic postoperative pain 3 months after surgery. No single‐nucleotide polymorphisms reached genome‐wide significance, but several showed suggestive associations with chronic postoperative pain (p < 1 × 10 −5 ). Single‐nucleotide polymorphisms with significance p < 1 × 10 −5 were followed up in a replication cohort consisting of 203 men and women scheduled for orthopaedic or abdominal surgery. Ten of these patients developed severe chronic postoperative pain. A single‐nucleotide polymorphism in NAV3 was significantly replicated with chronic postoperative pain in the replication cohort (p = 0.009). Meta‐analysis revealed that two loci ( IQGAP1 and CRTC3) were significantly associated with chronic postoperative pain at 3 months ( IQGAP1 p = 3.93 × 10 −6 β = 2.3863, CRTC3 p = 2.26 × 10 −6, β = 2.4209). The present genome‐wide association study provides initial evidence for genetic risk factors of chronic postoperative pain and supports follow‐up studies.